2018
DOI: 10.1007/s10344-018-1216-8
|View full text |Cite
|
Sign up to set email alerts
|

Overwinter survival and post-release movements of translocated water voles: implications for current mitigation guidance

Abstract: Translocation is currently used as a last resort mitigation strategy for water voles (Arvicola amphibius) in the UK (Dean et al. 2016, The Water Vole Mitigation Handbook), where populations have undergone widespread declines during the past century Q214 (Strachan and Jefferies1993, Preliminary report on the changes in the water vole as shown by the National Surveys of1989-1990 and 1996-1998). To increase the chances of success, current guidance suggests translocation of voles during autumn should not be carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Moreover, Moorhouse & Macdonald (2005) concluded that female water voles exhibit drifting territoriality, and the degree to which territories drifted was smaller at higher densities. Results of recent studies conducted in U.K. showed, similarly to our results, that activity of resident water vole males was about twofold higher than activity of resident females (Baker et al 2018). Mean weekly distance between two locations was about 30 m in males and 15 m in females, and maximum weekly distance was about 315 m in males and 70 m in females.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Moorhouse & Macdonald (2005) concluded that female water voles exhibit drifting territoriality, and the degree to which territories drifted was smaller at higher densities. Results of recent studies conducted in U.K. showed, similarly to our results, that activity of resident water vole males was about twofold higher than activity of resident females (Baker et al 2018). Mean weekly distance between two locations was about 30 m in males and 15 m in females, and maximum weekly distance was about 315 m in males and 70 m in females.…”
Section: Discussionsupporting
confidence: 90%
“…For a semi-aquatic mammal, focusing on methods within their main foraging medium appears highly beneficial. Traps mounted to floating platforms have been successful in trapping water voles (Arvicola amphibius), muskrats (Ondatra zibethicus and Neofiber alleni), South American water rats (Nectomys squamipes), water opossums (Chironectes minimus), mink (Neovision vison) and spot-legged turtles (Rhinoclemmys punctularia) (Schooley and Branch 2005;Ahlers et al 2010;Harrington et al 2012;Leite et al 2016;Lima et al 2016;Baker et al 2018;Garcia-Passos et al 2018). However, the use of cameras overlooking such platforms has not been previously reported and provides a successful novel method.…”
Section: Discussionmentioning
confidence: 99%
“…However, camera traps have successfully detected semi-aquatic species when positioned at a distance from the water, at haul-out areas, and latrine sites (Day et al 2016;Findlay et al 2020;Gil-Sánchez and Antorán-Pilar 2020). Other specialised methods are often adopted to detect semi-aquatic mammals, such as pressure-plate activated camera traps, or cage traps adapted to be deployed in the water (Lerone et al 2015;Baker et al 2018). The use of environmental DNA sequencing has also been demonstrated as a powerful tool in detecting semi-aquatic mammals, particularly in comparison with alternate methods (Sales et al 2020;Brunt et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on fossorial voles are needed to characterise male and female home ranges in both early spring prior to breeding and when breeding, and across a range of habitats and seasons to fully understand spatial use. Furthermore, urban open space is often redeveloped for housing and relocation of water voles to donor sites is used to mitigate impacts on local populations (Dean et al 2016;Baker et al 2018). Future research should therefore consider tracking water voles in response to development in other urban areas where water voles occur.…”
Section: Discussionmentioning
confidence: 99%